The Relationship Between Vision and Organizational Readiness for Change: The Mediating Effects of Empowerment and Trust in the Leader (Journal of Organizational Psychology, 2020)
Purpose – The purpose of this paper is to investigate the relationship between vision and readiness for organizational change directly and through the mediating effects of empowerment and trust.Design/methodology/approach – Data were collected from a sample of 409 managerial and non-managerial personnel from four business organizations. Structural equation modeling (SEM) was used to test direct and mediating effects.Findings – Analyses provided strong support for the direct effects of vision and organizational readiness for change and the effects of vision on readiness for change were mediated by empowerment and trust in the leader.Research limitations/implications – Vision is significantly associated with readiness for organizational change. However, both trust in leadership and sense of empowerment strengthen the relationship between the two variables.Practical Implications – A compelling vision can improve employees’ readiness for change by empowering them and by developing trust in the leader.Originality/value –To the authors’ knowledge, this is the first study to examine the mediating effects of trust and empowerment on the relationship between vision and organizational readiness for change.
Keywords: Organizational Psychology; vision; empowerment; readiness for change; trust; vision and readiness for change; Purpose; Design/methodology/approach; Findings; Research limitations/implications; Originality/value; Practical Implications